The complete mitochondrial DNA sequence of the pantropical earthworm Pontoscolex corethrurus (Rhinodrilidae, Clitellata): Mitogenome characterization and phylogenetic positioning - Conrado, Ana C. (Zookeys, 2017)
Abstract. Pontoscolex corethrurus (Müller, 1857) plays an important role in tropical soil ecosystems and has been widely used as an animal model for a large variety of ecological studies in particular due to its common presence and generally high abundance in human-disturbed tropical soils. In this study we describe the complete mitochondrial genome of the peregrine earthworm P. corethrurus. This is the first record of a mitochondrial genome within the Rhinodrilidae family. Its mitochondrial genome is 14 835 bp in length containing 37 genes (13 protein-coding genes (PCG) 2 rRNA genes and 22 tRNA genes). It has the same gene content and structure as in other sequenced earthworms but unusual among invertebrates it hasseveral overlapping open reading frames. All genes are encoded on the same strand. Most of the PCGs use ATG as the start codon except for ND3 which uses GTG as the start codon. The A+T content of the mitochondrial genome is 59.9% (31.8% A 28.1% T 14.6% G and 25.6% for C). The annotated genome sequence has been deposited in GenBank under the accession number KT988053.